Essential oils from Schinus Species of Northwest Argentina: composition and antifungal activity - Sampietro, Diego Alejandro (2014)
The composition of the essential oils from leaves (Sal) and fruits of S. areira (Saf), and fruits of S. fasciculatus (Sff) and S. gracilipes (Sgf) were analyzed by GC/MS. The major compounds identified were sabinene (26.0 +/- 0.5%), bicyclogermacrene (14.5 +/- 0.4%), and E-citral (6.7+/- 0.2%) in Sal oil, limonene (27.7 +/- 0.7%), sabinene (16.0+/- 0.5%), beta-phellandrene (14.6 +/- 0.8%) and bicyclogermacrene (8.1 +/- 0.2%) in Saf oil, sabinene (22.7 +/- 0.6%), alpha-phellandrene (18.7 +/- 0.3%), beta-phellandrene (15.7 +/- 0.4%), and bicyclogermacrene (8.1 +/- 0.2%) in Sff oil and beta-pinene (25.4 +/- 0.8%), alpha-pinene (24.7 +/- 0.7%), and sabinene (13.6 +/- 0.4%) in Sgf oil.The antifungal activity of the four oils was evaluated on strains of Fusarium verticillioides and F. graminearum, and the results compared with the effect of epoxyconazole, pyraclostrobin and thyme oil. The Sff oil had the highest antifungal activity among the Schinus oils tested, with MIC100 (F. graminearum) = 6 per thousand and MIC100 (F. verticillioides) = 12 per thousand. A principal component analysis suggests that 9 constituents (alpha-thujene, alpha-terpinene, p-cymene, gamma-terpinene, terpinolene, 1-terpineol, alpha-calacorene, alpha-phellandrene, and terpinen-4-ol) explain the higher antifungal effect of Sff. The MIC100s of Schinus oils were on average 30-60 and 8.5-17 fold lower than those obtained for thyme oil on F. verticillioides and F. graminearum, respectively. In the case of commercial fungicides, their MIC100s were three orders of magnitude lower than those of Schinus oils. The last ones showed an additive interaction when assayed in mixtures with the commecial fungicides and thyme oil. The results suggest that the doses of fungicides required for control of the Fusarium species can be reduced when they are assayed in mixtures with the Schinus oils.